Developing a Model for Evaluation and Accreditation of Hospitals - AM Mosadegh Rad; M Ansarian (Tehran University of Medical Sciences, 2005)
Background: Evaluation and accreditation of Health Care organizations has an important role in increasing the effectiveness and efficiency of these organizations and developing the quality of services provided. The current system of evaluation and accreditation of hospitals in Iran is based on structure only with out considering the context, process and output and this cause many problems for both health care providers and customers. Therefore, there is a pressing need for developing a model for health care systems' evaluation and accreditation, which help these organizations to improve the quality of services. Method: The aim of this article is therefore: "To identify the strengths and weakness of the current system of evaluation and accreditation of hospitals in Iran, determining the ideal system of evaluation and accreditation to develop a model so that health care organizations aiming at achieving effectiveness and efficiency". A descriptive study using a cross-sectional survey for data collection performed. All of hospital managers and hospital evaluators in Isfahan province were studied via a self administrated questionnaire (53 managers and 30 evaluators). This questionnaire specifies the respondents' opinions about the current and ideal system of evaluation and accreditation of hospitals. Data was analyzed via SPSS11 software. Findings: The mean score of current system of evaluation and accreditation of hospitals was 3.12 0.83 and 4.41 0.34 (in a 5 scale).The mean score of structure, process and outcome were 3.10.73, 3.120.91and 3.091 in the current system of hospital evaluation respectively. From the view points of hospital managers and evaluators the differences between values of current and ideal scores of evaluation and accreditation system were statistically significant (P< 0.05). Therefore, there is a need for developing a model for hospital evaluation and accreditation. Based on these results an empirical model for Evaluation and Accreditation of Hospitals is developed. In this model, the context, structure (input), process and results (out put) were considered comprehensively. In this model items such as customer participation in treatment process, hospital information system, equity of services, employees' participation in evaluation process, increasing employees and managers knowledge and capabilities level, risk and safety management and so on are considered. Discussion: The evaluation and accreditation system of Hospitals should be a comprehensive system in order to evaluate the whole dimensions of these organizations.